TRAINING IN HEARING HEALTH: STOCK RESULTS IN HEALTH EDUCATION IN THE CITY OF MACAÉ/RJ. (Fiep Bulletin - online, 2016)
In Brazil, there are about 9 million deaf and it is important to carry out activities in health education for the hearing health prevention and promotion and to improve the quality of life of this population. The objective was to present the activities and results of hearing health training conducted with community health workers (CHW) of Macaé. In a previous meeting have been defined with the Primary Care Management Health Macaé six training between December 2014 and May 2015, aimed at all community health workers. The training had the following schedule: Opening; Groups dynamics: "The five senses"; Lecture: "Anatomy and Physiology of Hearing" with a QUIZ the end; coffee break; Lecture: "Organization of Care Network Hearing Health Macaé"; QUIZ end for evaluation of knowledge. As speakers participated scholars, tutors and teachers of PET Health Saudi/Care Networks Hearing Health. Two hundred and forty CHW were trained in a total of four training. The activities proposed in the training were well received by CHW, noting that 100% got the statements presented in the QUIZ, referring to talk of Anatomy and Physiology of Hearing; and 90% got the final QUIZ, aimed at assessing the knowledge acquired throughout the training. Most CHW performed well in the assessment of knowledge, with exchange of experiences and interests of the professionals on the topic discussed.
Keywords: Educação em Saúde; Saúde Auditiva; Prevenção; Promoção da Saúde.